Spectroscopic and photometric analysis of symbiotic candidates – I. Ten candidates on classical symbiotic stars. Issue 3 (16th July 2021) - Merc, J; Gális, R; Wolf, M; Velez, P; Buil, C; Sims, F; Bohlsen, T; Vrašťák, M; Boussin, C; Boussier, H; Cazzato, P; Diarrasouba, I; et al.
ABSTRACT: Symbiotic stars belong to a group of interacting binaries that display a wide variety of phenomena, including prominent outbursts connected with mass transfer, as well as stellar winds, jets, eclipses, or intrinsic variability of the components. Dozens of new symbiotic stars and candidates have been discovered in recent years. However, there are many objects that are still poorly studied. Some symbiotic candidates suspected in the literature have never been studied spectroscopically. In this contribution, we present the first results of the ongoing campaign focused on symbiotic candidates. In the first paper in the series, we study the nature of 10 candidate classical symbiotic stars suspected based on their photometric behaviour, colours or abundance pattern. To confirm or reject the symbiotic nature of the studied candidates, we obtained new spectra and analysed them in detail together with available multifrequency photometric and spectroscopic observations of the objects. Hen 3−860 and V2204 Oph are genuine symbiotic systems showing typical spectral features of burning symbiotic stars and outbursts in the last 100 yr. The first object belongs to the uncommon group of eclipsing symbiotic stars. V1988 Sgr cannot be classified as a genuine burning symbiotic star, but the scenario of an accreting-only symbiotic system cannot be ruled out. Hen 4−204 might be a bonafide symbiotic star due to its similarity with the known symbiotic binary BD Cam. Six other symbiotic candidates (V562 Lyr, IRAS 19050+0001, EC 19249−7343, V1017 Cyg, PN K1−6, V379 Peg) are either single dwarf or giant stars or non-symbiotic binaries.